Two isolation treatments on the COVID-19 model and optimal control with public education - Rois, Muhammad Abdurrahman; Fatmawati, Fatmawati; Alfiniyah, Cicik (Jambura Journal of Biomathematics (JJBM), 2023)
This study examines a COVID-19 mathematical model with two isolation treatments. We assume that isolation has two treatments: isolation with and without treatment. We also investigated the model using public education as a control. We show that the model has two equilibria based on the model without control. The basic reproduction number influences the local stability of the equilibrium and the presence of an endemic equilibrium. Therefore, the optimal control problem is solved by applying Pontryagin's Principle. In the 100th day following the intervention, the number of reported diseases decreased by 85.5% when public education was used as the primary control variable in the simulations.